Pengaruh Konsep Health Tourism Terhadap Motivasi Kunjungan Wisata ke Sari Ater - Diny Nurul Fitriany; Titing Kartika (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2022)
This study aims to determine: (i) the concept of health tourism in Sari Ater; (ii) motivation for tourist visits to Sari Ater; (iii) the influence of the concept of health tourism on the motivation for tourist visits to Sari Ater. The method used in this research is quantitative by distributing questionnaires to a sample of 100 Sari Ater tourists randomly. The results of the questionnaire were processed using the SPSS 24 application by testing the validity, reliability, normality, simple linear regression, t test, and the coefficient of determination. The hypothesis of this study is